Mushroom Consumer Behaviour: Dimensions and Measurement Model - Shirur, Mahantesh; Shivalingegowda, N S; Chandregowda, M J; ., Preethi (Mushroom Research, 2017)
Mushrooms are known world over for their nutritional and medicinal importance. Even as the mushroom production and consumption are on the rise in rest of the world, India witnesses a lukewarm response in its growth. The mushroom consumer behaviour though is scarcely studied in India, is of considerable value to mushroom producers and people involved in mushroom marketing and processing. , the present study was envisaged to develop a scale to assess the mushroom consumption behaviour covering five major dimensions influencing the mushroom consumption by following psychometric technique using normalised rank approach. Based on the study, the Mushroom Consumer Behaviour Index (MCBI) was developed for application in mushroom consumer behaviour research. Among the five dimensions of the scale, the Situational dimension assumed highest scale value (5.93) followed by Dietary preferences (4.98), Economic dimension (4.62), Psychological dimension (4.25) and lastly the Social dimension assuming the least value (4.09). The scale developed will find utility for analysing the mushroom consumption behaviour across different regions and different sections of the society and to draw suitable conclusions by the researchers and the policy makers.